Financial Analysis of Beekeeping Practices at Acacia crassicarpa Plantation Forest in Riau Province, Indonesia - Pribadi, Avry; Kurniawan, Hery; Junaedi, Ahmad Junaedi; Yunianto, Andhika Silva; Wiratmoko, Michael Daru Enggar; Wahyuningsih, Siti; Novriyanti, Eka; Aswandi; Kholibrina, Cut Rizlani; Roza, Delvia (Jurnal Manajemen Hutan Tropika, 2023)
One environmental service provided by A. crassicarpa plantation is extrafloral nectar which has been widely used for beekeeping since 2019. Nevertheless, nowadays between apiaries practiced unfair competition since there were price fall led by oversupply and low demand after covid pandemic ended. Thus, evaluating the cost structure, profitability, and its feasibility value are critically required. The study's objectives were to 1) evaluate cost structure, revenue and profitability and 2) to conduct a feasibility analysis of each apiary type. This study was conducted from in 2019 to 2022 at the Siak Regency, Riau, Indonesia. Structure interviews combined with desk studies were carried out to collect the data. Data were analyzed based on cost structure, revenue, profitability, and feasibility analysis. All types of apiaries were feasible since they could cover variable and fixed costs. However, it revealed that all types of apiaries experienced minus in profitability in the fourth of financial year. In general, variable cost relatively increased to the level of 50% of total cost in the fourth year. In contrast, fixed cost was relatively declined to less than 50%. Apiaries managed two rits had a better performance in cost structure to face the competitive market followed by apiaries managed three rit. Meanwhile, apiaries managed rit one experienced such a difficult challenge to survive.